Kermit's swamp years - Peruggi, Ritamarie; Lewis, Jim.; Mazzarino, Joseph; Gumpel, David; Hostetter, John.; Bookston, William; Lintz, Kelly Collins; Barretta, Bill.; Kennedy, John.; Dinnean, Alice; Summer, Cree.; Whitmire, Steve, 1959-; et al. (Culver City, Calif. : Columbia TriStar Home Entertainment, 2002)
Young Kermit is a curious, fun-loving frog who likes hanging out with his amphibious best friends. He loves the swamp, but wonders what lies beyond the tall marsh grass. When one of Kermit's friends gets nabbed by a pet store owner, Kermit leaps into action, leaving the swamp and racing to rescue his friend.
Director of photography, Rufus Standefer ; editor, Katina Zinner ; music, Joe Carroll, Peter Thom ; production designer, Orvis Rigsby ; Muppet character designer, Edward Eyth.
John Hostetter, William Bookston, Kelly Collins Lintz ; Voices: Bill Barretta, Joseph Mazzarino, John Kennedy, Alice Dinnean, Cree Summer, Steve Whitmire.
MPAA rating: G.
Digital, Dolby surround.
Closed-captioned.
Keywords: Kermit the Frog (Fictitious character) -- Juvenile drama; Swamps -- Juvenile drama; Frogs -- Juvenile drama; Feature films; Children's films; Films for the hearing impaired